The Influence of Participative Leadership on Cooperative Member Loyalty: The Mediating Role of Helping Behaviour and Trust in Leaders - Iwang Suwangsih; Nindya Kartika Kusmayati; Dhiyan Septa Wihara; Dini Febriani (Universitas Hamzanwadi, 2025)
This study examines the influence of participative leadership style on cooperative member loyalty with trust in leaders and helping behavior as mediating variables. Cooperatives, as pillars of the Indonesian economy, require effective leadership to strengthen member commitment and sustainability. The novelty of this research lies in its focus on cooperative groups whose members join voluntarily, and in integrating social exchange theory to explain leadership dynamics. Using a quantitative explanatory design, data were collected from 217 respondents representing groups of the Setia Bhakti Wanita Cooperative in Surabaya. Data analysis was conducted with Structural Equation Modeling (SEM) using SmartPLS 3. The results show that participative leadership has a significant positive effect on trust in leaders, helping behavior, and member loyalty. Helping behavior was also found to significantly mediate the relationship between participative leadership and loyalty, while trust in leaders did not play a significant mediating role. These findings highlight that loyalty is better fostered through collective prosocial actions rather than solely relying on trust in leaders. Practically, cooperative leaders are encouraged to apply participative leadership that emphasizes member involvement in decision-making, open communication, and a culture of mutual assistance to build sustainable loyalty. Future research is recommended to expand the object of study across different cooperative contexts and include other mediating variables such as member satisfaction or organizational commitment to enrich the understanding of member loyalty.